2008
DOI: 10.1086/523836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baryons and Dissipation on the Matter Power Spectrum

Abstract: We study the importance of baryonic physics on predictions of the matter power spectrum as it is relevant for forthcoming weak lensing surveys. We quantify the impact of baryonic physics using a set of three cosmological numerical simulations. Each simulation has the same initial density field, but models a different set of physical processes. The first simulation evolves the density field using gravity alone, the second includes non-radiative gasdynamics, and the third includes radiative heating and cooling o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
527
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(560 citation statements)
references
References 106 publications
29
527
4
Order By: Relevance
“…Jing et al (2006), Rudd et al (2008), Guillet et al (2010), Casarini et al (2012) all confirmed the significance of baryonic feedback at k > 1h Mpc −1 by comparing hydrodynamical simulations to pure N-body dark matter ones. Schaye et al (2010) .…”
Section: Baryonic Feedbackmentioning
confidence: 57%
“…Jing et al (2006), Rudd et al (2008), Guillet et al (2010), Casarini et al (2012) all confirmed the significance of baryonic feedback at k > 1h Mpc −1 by comparing hydrodynamical simulations to pure N-body dark matter ones. Schaye et al (2010) .…”
Section: Baryonic Feedbackmentioning
confidence: 57%
“…The power spectrum can then be calculated by providing the mass of the central galaxy (through abundancematching), its size, the total gas mass as a fraction of the total halo mass, and an adiabatic contraction for the cold dark matter. This model has been developed over a number of years [303,304,305,306,307,308,309], and has been found to agree well with zooming hydrodynamical simulations [310]. One can then use such models to marginalize over baryonic effects in surveys, e.g.…”
Section: Simulating the Universementioning
confidence: 90%
“…Therefore one should worry that the removal of baryonic physics-induced bias seen by Semboloni et al (2011) might not be realized in practice, if the simulation captures the qualitative features of AGN feedback but does not quantitatively reproduce the correct functional form. Zentner et al (2012) avoid this issue by fitting cosmic shear power spectra based on the van simulations using a mitigation procedure tuned to the Rudd et al (2008) simulations. However they find that this procedure, while successful on simulated Stage III (DES) survey data, is not adequate for the more ambitious task of Stage IV data analysis.…”
Section: Intrinsic Alignments*mentioning
confidence: 99%